A Checklist of Short-horned Grasshopper Species (Orthoptera: Caelifera) from Littoral Region of Cameroon with description of a new species of the genus Hemierianthus Saussure, 1903 (Orthoptera: Chorotypidae) - Yetchom-Fondjo, Jeanne Agrippine; Kekeunou, Sévilor; Kenne, Martin; Missoup, Alain Didier; Huang, Huateng; Ma, Libin; Xu, Sheng-Quan (Zootaxa, 2019)
The Littoral Region of Cameroon is one of the most highly disturbed regions in Cameroon that remain poorly studied and where no investigation regarding the grasshopper fauna has been conducted. Hence a survey was conducted from August 2015 to November 2018 in 11 localities of this region. In each locality, grasshoppers were sampled in three vegetation types (forests, fallows and cultivated farms) using sweep nets sampling method. We collected in total 51 short-horned grasshopper species belonging to the families Acrididae, Chorotypidae, Euschmidtiidae, Pyrgomorphidae and Thericleidae. Among these species, 43 belong to Acrididae, 5 to Pyrgomorphidae and only one belongs to the Chorotypidae, Euschmidtiidae and Thericleidae respectively. The Chorotypidae species Hemierianthus mbongueensis Yetchom & Xu sp.nov. is also described in this study. Twelve grasshopper species were widely distributed as they occurred in all study sites and 11 were recorded exclusively from one study site. This study showed that there is high species richness of short-horned grasshoppers in the Littoral Region of Cameroon. However, more sampling effort in different ecosystems of this region and other regions of Cameroon will certainly improve our understanding on grasshopper taxonomy, ecology and biogeography.